Establishing a Nexus between Sharing Economy and Entrepreneurial Sustainability: A Conceptual Perusal - Mishra, Vivek (AMC Indian Journal of Entrepreneurship, 2017)
In the entrepreneurial framework, the individual-opportunity connection forms the core of the progression; however sustainability, scalability, and growth pose major challenges. In order to optimize sustainability, entrepreneurs must begin with a proper understanding of the necessary conditions that must be emphasized upon, for their business models to achieve livability. Entrepreneurs are best positioned to develop practical solutions to these problems by sharing goods, services, or knowledge. This economy is termed as sharing economy, and is also dubbed as collaborative consumption. The tremendous growth potential of the sharing economy is hinting at a paradigm shift in the historical model of consumption. From a potential roadmap to sustainability, shared economy is also contradictorily considered to be a worsening of wealth inequality and a race to the bottom. These constructs however, share a collective vision of the sharing economy, as an agreement based on trust,a forte of innovation, and as a disruption of customary technical and economic arrangements.This conceptual paper explored how the concept of a shared economy leads to entrepreneurial sustainability and growth. It builds on the assumption that the creation of sustainable practices is one of the most important challenges facing the start-up scenario and that the sharingeconomy platform is a keymechanism in the pursuit of sustainability.The main objective of this article is to study the sustainability potential of the sharing economy, and the conditions crucial for the realization of this potential.